If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + b = 160z Solving a + b = 160z Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1b' to each side of the equation. a + b + -1b = -1b + 160z Combine like terms: b + -1b = 0 a + 0 = -1b + 160z a = -1b + 160z Simplifying a = -1b + 160z
| 4(m+2)-7= | | 13t+9+2t-9= | | 4(m+2)-7=a | | 14t+9+2t-9= | | -0.8*x^3-0.6*x-2.1=0 | | 64+88+8x=10x+14x+(8x+4) | | 3s-42=-3a-12 | | 23t+9+2t-9= | | 3x+9y=-27 | | 5(t+1)=-5 | | 32-4x=5-7x | | 9x+22+6-7=180 | | -logx=6.6 | | z^2+(8-i)*z-8*i=0 | | 2e+1=21-8e | | 6x+13=-35-2x | | .10x+2=.05x+3.95 | | -10.53+18.9v=8.3v-5.07+11.9v | | 10000=x-.15x | | 5x-19=3x+23 | | C*.75+D*.40=265.00 | | 2(3s+7)=80 | | 1+8x=-27+x | | 6(2l+3)=42 | | b-12+5b-4= | | 16=5x | | 4c=2c^2+8 | | 1+8x=-27x | | 2(7x+4)+-1(3x+-9)=3(2x+10)+8 | | -2x-2+6x=-26 | | 4(a-3)=72 | | 2x+7+3x-17=90 |